Sensitization, epileptic-like symptoms and local synchronization in patients with paranoid schizophrenia - Bob, Petr; Palus, Milan; Susta, Marek; Glaslova, Katerina (Progress in neuro-psychopharmacology & biological psychiatry, 2010)
Recent findings indicate that changes in synchronization of neural activities underlying sensitization and kindling could be more comprehensively understood using nonlinear methods. With this aim we have examined local synchronization using novel measure of coarse-grained information rate (CIR) in 8 EEG signals recorded at different cortical areas in 44 patients with paranoid schizophrenia. The values of local synchronization that could reflect sensitization related changes in EEG activities of cortical sites were then related to psychometric measures of epileptic-like symptoms and positive and negative schizophrenia symptoms (PANSS). While no significant correlations between CIR and positive and negative symptoms have been found, statistically significant relationships described by Spearman correlation coefficients between CIR indices and results of LSCL-33 have been observed in 7 (of 8) EEG channels (r in the range from 0.307 to 0.374, p<0.05). Results of this study provide first supportive evidence for the relationship between local synchronization measured by CIR and epileptic-like symptoms in schizophrenia.
Keywords: Cortical Synchronization; paranoidní schizofrenie; dospělí; mladý dospělý; korová synchronizace; Epilepsy; lidé; Female; epilepsie; mužské pohlaví; Young Adult; Male; Schizophrenia, Paranoid; elektroencefalografie; Adult; ženské pohlaví; Electroencephalography; Humans